غزوہ فتح مکہ: حدیث کی معنوی روایت اور قیام کی مدت کا تحقیقی جائزہ : The Conquest of Makkah: A Research Review of Hadith Narration in Meaning and the Duration of the Stay - Dr. Ayesha Tariq; Dr. Shaista Jabeen (International Research Journal of Arabic and Islamic Studies, 2024)
Hadith is the second main source of Islamic Law, valid forever. Hadith was transmitted in two ways. One is narration by words (Riwayat billafz) and the other is narration in the meaning (Riwayat bilmana). One group of Traditionalists opposes Hadith’s narration in the meaning while the other gives permission with some conditions.Orientalists have made objection on the narration of Hadith in the meaning. Side by side the non-muslims, one group from our so-called muslims claim the authenticity of Hadith. The study will certainly disperse the doubts and set aside the wrong impression regarding Hadith’s narration in the meaning. This article deals with the above mentioned issue in detail.